On mechanisms for high-frequency pump-enhanced optical emissions at 557.7 and 630.0 nm from atomic oxygen in the high-latitude F-region ionosphere - Leyser, Thomas B.; Sergienko, Tima; Brändström, Urban; Gustavsson, Björn; Rietveld, Michael T. (Annales Geophysicae, 2023)
The EISCAT (European Incoherent Scatter Scientific Association) Heating facility was used to transmit powerful high-frequency (HF) electromagnetic waves into the F-region ionosphere to enhance optical emissions at 557.7 and 630.0 nm from atomic oxygen. The emissions were imaged by several stations of ALIS (Auroral Large Imaging System) in northern Sweden, and the EISCAT UHF incoherent scatter radar was used to obtain plasma parameter values. The ratio of the 557.7 to 630.0 nm column emission rates changed from I5577/I6300≈0.2 for the HF pump frequency f0=6.200 MHz ≈4.6fe to I5577/I6300≈0.5 when f0=5.423 MHz ≲4fe, where fe is the ionospheric electron gyro frequency. The observations are interpreted in terms of decreased electron heating efficiency and thereby weaker enhancement at 630.0 nm for f0=5.423 MHz ≲ 4 fe. The emissions at 557.7 nm are attributed to electron acceleration by upper hybrid waves of metre-scale wavelengths that can be excited with f0=5.423 MHz ≲ 4 fe.